2013
DOI: 10.1103/physrevlett.110.077203
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Scaling of Intrinsic Gilbert Damping with Spin-Orbital Coupling inL10FePdPt Films: Experiments andAb InitioCalculations

Abstract: We have experimentally and theoretically investigated the dependence of the intrinsic Gilbert damping parameter α0 on the spin-orbital coupling strength ξ by using L10 ordered FePd1−xPtx ternary alloy films with perpendicular magnetic anisotropy. With the time-resolved magneto-optical Kerr effect, α0 is found to increase by more than a factor of ten when x varies from 0 to 1.0. Since changes of other leading parameters are found to be neglected, the α0 has for the first time been proven to be proportional to ξ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 51 publications
6
89
1
2
Order By: Relevance
“…The value of Gilbert damping constant for the present FeTaC thin film is found to be comparable to those reported in Fe-based magnetic thin films, such as FePd ternary alloy, 11 permalloy, 30 NiFe/CoFeB/CoFe multilayered sturucture 15 and (FeCo) 1−x Gd x . 8 However, the Mn-and Cobased thin films 6,7 have larger damping parameter as compared to the present film which could be understood on the basis of spin-orbit coupling.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The value of Gilbert damping constant for the present FeTaC thin film is found to be comparable to those reported in Fe-based magnetic thin films, such as FePd ternary alloy, 11 permalloy, 30 NiFe/CoFeB/CoFe multilayered sturucture 15 and (FeCo) 1−x Gd x . 8 However, the Mn-and Cobased thin films 6,7 have larger damping parameter as compared to the present film which could be understood on the basis of spin-orbit coupling.…”
supporting
confidence: 63%
“…The intrinsic contribution to the Gilbert damping parameter has been studied by tuning the strength of the spin-orbit coupling. 8,11,12 Recently, Ikeda et al 13 have reported that CoFeB-MgO based MTJ with PMA would be reliable for high-density non-volatile memory application due to its high thermal stability and efficiency towards STT technology. The investigation on magnetic dynamics, PMA and the apparent magnetic damping have been studied extensively in CoFeB based soft ferromagnetic thin film by ferromagnetic resonance (FMR) and time-resolved magneto-optical Kerr effect.…”
mentioning
confidence: 99%
“…using the equilibrium equation of the magnetization, [40] where θH is the polar angle of the applied magnetic field, which is 86 (for a positive magnetic field) in our measurements. A typical example of the HK fitting is shown in Supporting Information Figure S1 and HK ranges from and 2 is provided in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…3(d), the value of α eff gradually decreases with higher H and saturates at high fields [52]. The decreasing trend of α eff with H is attributed to the suppression of dephasing dynamics among magnetic domains [21,31], since multiple domains exist at low fields as indicated in Fig. 1(b) and the magnon-magnon scattering is less effective for perpendicularly magnetized samples [53].…”
mentioning
confidence: 99%
“…The uniform magnetization precession can be well modeled with Landau-Lifshitz-GilbertSlonczewski (LLGS) equation [7][8][9], where the Slonczewski torque term denotes the spin transfer torques (STTs), and the Gilbert damping parameter α determines the spin relaxation time [10] and is crucial for device performance [11][12][13][14]. The extrinsic Gilbert damping is due to nonlocal spin relaxation, such as spin pumping and magnon-magnon scattering, which can be tuned by artificial substrates, specially designed buffer and coverage layers [15][16][17][18][19][20][21], while the intrinsic Gilbert damping parameter α 0 is thought to arise from spin-orbit interaction (SOI) [22][23][24][25][26][27][28][29][30], and recently its quadratic dependence on SOI is demonstrated experimentally in FePtPd alloys [31].The α 0 describes the energy flow rate from spin to electronic orbital and phonon degrees of freedom through electron scattering, and has been studied in various theoretical models [22][23][24][25][26][27][28][29][30]. The breathing Fermi surface model [22] and torque-correlation model [23] based on first principle band structure calculations qualitatively match α 0 in soft magnetic alloys such as Fe, .…”
mentioning
confidence: 99%